2010
DOI: 10.1002/jcla.20357
|View full text |Cite
|
Sign up to set email alerts
|

Lectin affinity electrophoresis of serum alkaline phosphatase in metastasized breast cancer

Abstract: The use of serum alkaline phosphatase (ALP) isoenzymes as markers of breast cancer metastases and treatment efficacy has received little attention. Twenty-six breast cancer women (56+/-13 years, all post-menopausal) were prospectively evaluated during their first and third course of chemotherapy (4-week interval). Serum samples were analyzed for ALP isoenzymes (bone, liver, and intestine) using a lectin affinity electrophoresis kit (Hydragel 15 ISO-PAL, Sebia) adapted on a semi-automated Hydrasys system (Sebia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…The measured sensitivity and specificity for AP and ß-CTx to detect bone metastases in our study are partially contrary to results of earlier investigations: for example the sensitivity of AP is 67,0% and the specificity 100,0%, whereas ß-CTx are not able to verify the presence of bone metastases or the sensitivity/specificity of ß-CTx is only 53,0%/ 45,0% and concisely lesser than our results demonstrate [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 99%
“…The measured sensitivity and specificity for AP and ß-CTx to detect bone metastases in our study are partially contrary to results of earlier investigations: for example the sensitivity of AP is 67,0% and the specificity 100,0%, whereas ß-CTx are not able to verify the presence of bone metastases or the sensitivity/specificity of ß-CTx is only 53,0%/ 45,0% and concisely lesser than our results demonstrate [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 99%
“…ALP is synthesized in the liver and osteoblasts, and has been used as a specific biomarker for liver and bone. Previous studies revealed that ALP was a biomarker for the presence of bone metastases before their appearance on the bone scintigraphy [ 6 , 12 , 13 ]. In patients with BC, ALP was found to be a significant prognostic factor in bladder cancer with definitive radiotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Its bone-specific isoforms (bone-specific alkaline phosphatase, BAP) originates in osteoblasts that release large amounts of the enzyme when bone repair activity occurs, for example bone metastases. 8,9 In the last few decades, hundreds of studies have reported the clinical value of ALP/BAP in BC and a significant increase in serum ALP was observed, which had been demonstrated to predict bone and liver metastases. 10 Although studies have shown that ALP and BAP are predictors of metastasis and related to prognosis in BC, 3,4,[10][11][12][13] the prognostic values reported in some studies are still controversial, 11,[14][15][16][17] and no systematic review has been performed.…”
Section: Introductionmentioning
confidence: 99%